The Case of the Smiling Shark - Krailing, Tessa (Oxford Oxford University Press, 2014)
In The Case of the Smiling Shark, the Foxy and Co. gang - that's Daniel (Foxy), Jamal, Wesley and Marietta - are helping Mrs Gale to clear the pond. They find a shark...and it's smiling! TreeTops Fiction contains engaging novels from top authors and illustrators with the variety children need to develop a love of reading!
Include Illustrations
Keywords: Theft -- Children's stories, English -- Welsh language